"We Don't Like Unanswered Questions": Information Practices of Students Transitioning to Clinical Education - Schvaneveldt, Nena (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2025)
Objective – Health professions students are awash in large quantities of information, often conflicting, as they learn their professions. In order to navigate this information, librarians often engage with these students, usually in their didactic phase of education; however, the way students use information clinically may not be the same as the way they learn to do so in the classroom. This study investigated the information practices and experiences of health professions students early in the clinical phase of their education, in order to answer the following research questions: What are the information practices of health professions students at the transition to clinical education? How do these students understand how their practices have developed over their education?Methods – A purposive sample of learners from six health-focused professional programs participated in individual in-depth interviews, created timelines, and completed follow-up diary entries. The data were analyzed using inductive thematic analysis.Results – Students’ information practices are characterized by three themes. They are motivated to build competency to provide patient care; they operate in dual roles as student and clinician; and they navigate ambiguity, uncertainty, and doubt. They were able to describe the way they experienced information, problems they solved, and the development over time. Taken as a whole, this describes student experience with information as a method of making meaning from previous experience and learning with a focus on applying what they know and learn to improve patients’ lives and health.Conclusion – Insight into these students’ practices, including affective and social domains of practice, can inform librarian-led instruction and outreach within health professions and other professional programs. Linking education about information to students’ motivations to provide excellent patient care and their desire to operate scientifically in a world of doubt may provide more relevant instruction, leading to transference of learning to new environments.